2018
DOI: 10.1080/13506129.2018.1428795
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathological dimensions in subjects with hereditary ATTR V30M amyloidosis and their relation with life events due to the disease

Abstract: Results point to an important vulnerability of this population for psychological distress and psychiatric disease. Early life events related to disease, being sick and sex are associated with psychopathological distress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Sixty percent of patients and key relatives stated they cried or felt depressed in the past 2 months. These findings are in line with those reported by Lopes et al [16] about the prevalence of psychiatric problems in ATTRv patients and by Theaudin et al [12] on marital difficulties and depression in this disease. Feelings of sadness may lead to depression and other minor psychiatric disorders [18].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Sixty percent of patients and key relatives stated they cried or felt depressed in the past 2 months. These findings are in line with those reported by Lopes et al [16] about the prevalence of psychiatric problems in ATTRv patients and by Theaudin et al [12] on marital difficulties and depression in this disease. Feelings of sadness may lead to depression and other minor psychiatric disorders [18].…”
Section: Discussionsupporting
confidence: 93%
“…The familiar hereditary influence of ATTRv is reflected in the feeling of guilt of a possibility to pass the disease to offspring, as found in the 58.2% of the patients and 39.5% of their relatives. Moreover, it is likely that feelings of loss and worries about the future-frequently reported by patients and relatives in this study-subtend fear of death, sometimes observed in patients with ATTRv and their atrisk relatives [16,17,20]. Sixty-six percent of patients and 48.5% of family members were convinced that if the patient had not been ill everything would have been fine in their family.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…These descriptions are compatible with the differences noted between HC and AC in this study. Moreover, studies have shown that being a carrier of the V30M mutation, whether symptomatic or asymptomatic, is associated with more vulnerability to psychopathological symptoms and emotional distress (27), especially with the proximity to the age of onset which can trigger anxiety (28). In future gait analysis studies, the use of an anxiety measurement tool would therefore be very useful to complement the evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…The characteristic phenotype of this mutation comprises sensori-motor polyneuropathy of the legs, carpal tunnel syndrome, autonomic dysfunction, constipation, and impotence. [23] While the V122I TTR mutation is notable for its high prevalence in patients of African origin. Roughly 3% to 4% of African Americans are heterozygous for this mutation.…”
Section: Discussionmentioning
confidence: 99%